Restricted cell surface expression of receptor tyrosine kinase ROR1 in pediatric B-lineage acute lymphoblastic leukemia suggests targetability with therapeutic monoclonal antibodies. - Hema Dave; Miriam R Anver; Donna O Butcher; Patrick Brown; Javed Khan; Alan S Wayne; Sivasubramanian Baskar; Christoph Rader (PLoS ONE)
Background Despite high cure rates for pediatric B-lineage acute lymphoblastic leukemia (B-ALL), short-term and long-term toxicities and chemoresistance are shortcomings of standard chemotherapy. Immunotherapy and chemoimmunotherapy based on monoclonal antibodies (mAbs) that target cell surface antigens with restricted expression in pediatric B-ALL may offer the potential to reduce toxicities and prevent or overcome chemoresistance. The receptor tyrosine kinase ROR1 has emerged as a candidate for mAb targeting in select B-cell malignancies. Methodology and principal findings Using flow cytometry, Western blotting, immunohistochemistry, and confocal immunofluorescence microscopy, we analyzed the cell surface expression of ROR1 across major pediatric ALL subtypes represented by 14 cell lines and 56 primary blasts at diagnosis or relapse as well as in normal adult and pediatric tissues. Cell surface ROR1 expression was found in 45% of pediatric ALL patients, all of which were B-ALL, and was not limited to any particular genotype. All cell lines and primary blasts with E2A-PBX1 translocation and a portion of patients with other high risk genotypes, such as MLL rearrangement, expressed cell surface ROR1. Importantly, cell surface ROR1 expression was found in many of the pediatric B-ALL patients with multiply relapsed and refractory disease and normal karyotype or low risk cytogenetics, such as hyperdiploidy. Notably, cell surface ROR1 was virtually absent in normal adult and pediatric tissues. Conclusions and significance Collectively, this study suggests that ROR1 merits preclinical and clinical investigations as a novel target for mAb-based therapies in pediatric B-ALL. We propose cell surface expression of ROR1 detected by flow cytometry as primary inclusion criterion for pediatric B-ALL patients in future clinical trials of ROR1-targeted therapies.